Red Guava (Psidium guajava L.) Chemical Properties Characterization Using Different Packaging Methods During Storage - Rini Umiyati; Lustika Eva Lusiana; Iffah Muflihati; Fafa Nurdyansyah (University of Sultan Ageng Tirtayasa, 2022)
The limited shelf life of red guava fruit encourages efforts to maintain its shelf life by using the sealing and wrapping packaging method with storage at 9ºC for 12 days. The purpose of this study was to determine the effect of packaging method and storage time on the chemical properties of red guava (Psidium guajava L.). This study used a factorial design consisting of 2 factors. The first factor is the packaging method (without packaging, sealing and wrapping). The second factor is storage time (day 0, day 3, day 6, day 9 and day 12). The results showed that the highest vitamin C content was in the sealing packaging method, namely on the 3rd day of storage at 3.3%. the highest water content value is 90.45% on the packaging method of wrapping storage on day 0, the highest value of total titrated acid in fruit with packaging method of packaging storage day 0 is 0.08%, while the highest value of total dissolved solids was 7.33oBrix on the 12th day storage sealing packaging method.